Social Capital as a Determinant of Health in Older Adults: A Narrative Review - Ahadi Pradana, Anung (KnE Life Sciences, 2022)
Increasing life expectancy in relation to healthy aging can be a challenge for older adults and the risk of vulnerability increases. The social environment of the community is known to be one of the factors that has a major influence on the achievement of healthy aging in older adults through strengthening existing social capital. This research involved a simple literature study where articles were found by searching using the keywords ”social capital”, ”healthy aging”, ”elderly”, ”older adults” and ”active aging” in several databases such as Google Scholar, ProQuest, Wiley Online, PubMed, and ScienceDirect. The inclusion criteria included: (1) articles written in Indonesian or English; (2) published in 2011-2021; and (3) explaining the effect of social capital on older adults. Main reference articles such as those describing the social capital theories of R.D. Putnam, Simon Szreter, and Michael Woolcock were also examined. According to the results, the development of effective social capital in the community requires considerable costs and overcoming major challenges. However, the positive effect created is the emergence of new and more effective social networks that can promote a more meaningful social life, especially in older adults. Social capital is one of the most important factors in strengthening health perspectives in relation to the complexities of older adults’ health. Further studies on the negative effects of aging experienced in relation to social conditions need to be carried out by researchers and health workers. Keywords: health determinants, older adults, gerontology, social capital